A new C0 2D Fe model based on improved higher order zigzag theory for the analysis of soft core sandwich plate - Khandelwal, Ravi P.; Chakrabarti, Anupam; Bhargava, Pradeep (Zielona Góra: Uniwersytet Zielonogórski)
An efficient C0 continuous finite element (FE) model is developed based on a combined theory (refine higher order shear deformation theory (RHSDT) and least square error (LSE) method) for the static analysis of a soft core sandwich plate. In this (RHSDT) theory, the in-plane displacement field for the face sheets and the core is obtained by superposing a global cubically varying displacement field on a zig-zag linearly varying displacement field with a different slope in each layer.
Keywords: composites; finite element methods; plates; soft-core sandwich